"As it is an Evil": Defensive Equivocation in Measure for Measure. Issue 6 (18th August 2021) - Schumann, Angela; Groves, Peter
ABSTRACT: "Repent you, fair one, of the sin you carry?" – "I do; and bear the shame most patiently". Thus begins one of the most overlooked dialogues in Measure for Measure . Hidden in what appears to be an irrelevant rhetorical exercise in penitentiary pedagogy is in fact a covert battle of semantic appropriation and dissimulation which has largely gone unnoticed by audiences and critics alike. This paper seeks to address this gap through a close reading of the use of equivocation in Measure for Measure, grounded in the linguistic and theological controversies of Early Modern theology. This paper suggests that whilst the practice of equivocation seems to be condemned by Shakespeare elsewhere, in Measure for Measure he explores the liberating potential of Jesuitical discursive practices as a subtle probing of the very nature of truth, and as a means of defence against an unjust authority.